Density-Dependent Growth and Production of Nile Tilapia (Oreochromis niloticus) Fingerlings Relative to Phytoplankton and Periphyton Biomass (Our Nature, 2014)
The growth, production and survival of Nile tilapia Oreochromis niloticus, with an average individual weight of 0.2 g were used to determine the density-dependent growth and production relative to phytoplankton and periphyton biomass in periphyton-based aquaculture. The trial was conducted in 10 m2 concrete tanks for a 56 day period. A 10 cm layer of soil was placed at the bottom of each tank. To act as substrates for periphyton, bamboo poles with an approximate submerged surface area of 50% to that of the total tank surface area were vertically posted in the tank bottom. A weekly fertilizer dose of urea and triple superphosphate at a rate of 28 kg N and 7 kg P/ha/week was added. Four stocking densities in triplicate were used: 5, 10, 20, and 40 fish/m2 (50, 100, 200, and 400 fish/tank). The results indicated that the carrying capacity of periphyton-based tanks for Nile tilapia was 293 g/m2 in a 56-day culture period. The relationships between gross yields of tilapia (y) and periphyton dry matter (x), or chlorophyll a (x) were described as y = 353.2483-109.1809x, R2 = 0.5646, P = 0.005, y = 125.5916 + 0.9698x, R2 = 0.5841, P = 0.004. Provision of substrates at 50% of total tank surface area was sufficient for periphyton production in nutrient-rich aquaculture ponds where grazing rate and fish density in the system are balanced.DOI: http://dx.doi.org/10.3126/on.v11i2.9646 Our Nature 2013, 11(2): 105-115